Evaluating the impact of a national clinical leadership fellow scheme. Issue 2 (10th May 2019) - McKimm, Judy; Hickford, Donna; Lees, Peter; Armit, Kirsten
Abstract : Background: The drive towards engaging UK doctors in clinical leadership and management has involved a number of initiatives at various levels, including specific fellowships for doctors in training which enable them to take a year out of programme to work with senior leaders on service improvement or policy development projects. Objectives: This paper reports on the findings of an impact evaluation of a national Fellowship Scheme for doctors in training. The evaluation aimed to determine: What were the key success factors and areas for improvement of the Scheme? How did the Fellows experience the Scheme and how has this influenced their subsequent engagement, behaviours and thinking about healthcare leadership and management? What was the perceived impact of the Scheme? Participants: Six cohorts of Fellows and key stakeholders were involved in the evaluation . Results: The evaluation has clearly demonstrated the impact of this long-standing national Fellowship Scheme and the huge benefits for the individuals and organisations involved. For the Fellows, a national scheme such as this provides a unique experience, allowing them to learn first-hand from a range of senior decision-makers and engage in policy and strategic developments and processes. Conclusions: This evaluation has demonstrated the wide impact of the Scheme but has also highlighted that more evaluations are needed of the wide range of fellowship schemes on offer to evidence broader impact, and raised issues around some of the difficulties these Fellows encounter on their return to practice in using their new skills to engage in service and healthcare improvement initiatives.